Analysis of Diarrhea Cases with Oralit Administration in Kalimantan Timur in 2020-2023 - Waode Nesa Nur Fadilah; Wilna Damayanti; Wa Ode Yusriani; St Nurhaliza Artika Sari; Ummu Adawiyah (Journal of Epidemiology and Health Science, 2025)
Background: Diarrhea is a significant public health problem, especially in developing countries like Indonesia. According to the World Health Organization (WHO), more than 1.7 billion cases of diarrhea occur each year, with around 760,000 deaths of children under the age of five. In Indonesia, the high incidence of diarrhea is mainly associated with poor sanitation conditions and limited access to basic health services. One of the main interventions in treating diarrhea is the administration of oral rehydration salts (ORS), which functions to replace lost body fluids and prevent dehydration. Objective: This study aims to analyze the relationship between the number of diarrhea cases and the coverage of oralit provision in Provinsi Kalimantan Timur, as well as to identify areas with low intervention as a basis for formulating health policies. Method: This study is a quantitative descriptive study with secondary data analysis obtained from   Provinsi Kalimantan Timur  Health Office and the national health information system in the period 2020–2023. Results: There is an imbalance between the incidence of diarrhea and the coverage of oralit provision in several areas. Paser and Kutai Barat districts show low coverage of oralit despite high diarrhea rates. In contrast, Balikpapan and Samarinda cities show high coverage along with good access to health services. Conclusion: Increasing the distribution of oralit and public education are the keys to reducing diarrhea rates in Kalimantan Timur.